1975
DOI: 10.1007/bf02532440
|View full text |Cite
|
Sign up to set email alerts
|

Lipid profiles of plasma lipoproteins of fasted and fed normal and choline‐deficient rats

Abstract: Three major density classes of lipoproteins and a residual protein (d greater than 1.21) were isolated by ultracentrifugation from plasma of fasted, fed normal, and choline-deficient rats. Lipid extracts were obtained from total plasma and the various density classes of lipoproteins, and each extract was examined in detail by thin layer and gas chromatographies. The results indicated essentially identical compositions of molecular species of phosphatidyl choline, which suggested their rapid equilibration amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
11
0

Year Published

1990
1990
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(12 citation statements)
references
References 46 publications
1
11
0
Order By: Relevance
“…Methyl depletion as a consequence of niacin toxicity has been confirmed by the observations that hepatic toxicity can be prevented by choline and betaine supplements. 30,55 It is known that methyl deficiency may limit the formation of very low density lipoprotein and low density lipoprotein in the liver due to decreased phosphatidylcholine synthesis, which may result in a decrease in the levels of plasma very low density lipoprotein and low density lipoprotein, as demonstrated in rats by Mookerjea et al 56 On the other hand, the decreased transport of fat from the liver may lead to an accumulation of fat in the liver, and as a result, fatty liver and steatosis may occur. 57 Moreover, adequate phosphatidylcholine is also required for the formation and clearance of chylomicrons from the intestinal mucosa.…”
Section: Arsenicmentioning
confidence: 99%
See 1 more Smart Citation
“…Methyl depletion as a consequence of niacin toxicity has been confirmed by the observations that hepatic toxicity can be prevented by choline and betaine supplements. 30,55 It is known that methyl deficiency may limit the formation of very low density lipoprotein and low density lipoprotein in the liver due to decreased phosphatidylcholine synthesis, which may result in a decrease in the levels of plasma very low density lipoprotein and low density lipoprotein, as demonstrated in rats by Mookerjea et al 56 On the other hand, the decreased transport of fat from the liver may lead to an accumulation of fat in the liver, and as a result, fatty liver and steatosis may occur. 57 Moreover, adequate phosphatidylcholine is also required for the formation and clearance of chylomicrons from the intestinal mucosa.…”
Section: Arsenicmentioning
confidence: 99%
“…Similarly, choline deficiency has been demonstrated to lower the level of plasma chylomicrons. 56 Interestingly, niacin has been found to induce both lipid-lowering effect 52 and adverse hepatic outcomes. 46,52,54,55 Thus, it seems that the lipidlowering effect of niacin may be mediated by methyl depletion, which, although improving cardiovascular outcomes, may increase the risk of adverse hepatic outcomes.…”
Section: Arsenicmentioning
confidence: 99%
“…Although choline deficiency reduces plasma TG in both male and female rats, the response is more pronounced in males (26). These observations led to the widely held view that the development of fatty livers in animals fed a CD diet is the result of an impaired hepatic secretion of TG into plasma lipoproteins, primarily VLDLs, because of inhibition of PC synthesis from choline (24,25,27,28,30,31).To determine whether the reduction in plasma TG induced by choline deficiency in rats was the result of impaired lipoprotein secretion, rather than increased removal of TGs from plasma, Yao and Vance (17, 32) examined VLDL secretion by CD and CS primary rat hepatocytes. The hepatocytes were isolated from rats fed a CD diet for 3 days and subsequently incubated in medium containing or lacking choline and methionine.…”
mentioning
confidence: 99%
“…Although choline deficiency reduces plasma TG in both male and female rats, the response is more pronounced in males (26). These observations led to the widely held view that the development of fatty livers in animals fed a CD diet is the result of an impaired hepatic secretion of TG into plasma lipoproteins, primarily VLDLs, because of inhibition of PC synthesis from choline (24, 25,27,28,30,31).…”
mentioning
confidence: 99%
“…1) might be evoked through the alteration of hepatic phospholipid composition, e.g., a decrease in the ratio of phosphatidylcholine (PC) to phosphatidylethanolamine (PE), in rats fed on a cholesterol-free diet. Choline defici ency 12,13) and dietary supplementation with PE 14) or ethanolamine 15 ) are also shown to reduce plasma cholesterol with a concomitant decrease in the PC/PE ratio of the rat liver. Further, Mogami-Nishimaki et al 16 ) have recently demonstrated that some hypocholesterolemic drugs such as clofibrate and bezafibrate could decrease the PC/PE ratio of cultured rat hepatocytes and thereby reduce the secretion of very low-density lipoprotein (VLDL) from the cells.…”
mentioning
confidence: 95%